2019
DOI: 10.1016/j.ejvs.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Stent Graft Motion in ECG Gated CT by Image Registration and Segmentation: In Vitro Validation and Preliminary Clinical Results

Abstract: WHAT THIS PAPER ADDS The present article establishes a novel method to quantify and visualise stent graft motion in multiphasic ECG gated computed tomography using image registration techniques. In vitro validation demonstrated adequate accuracy for quantifying abdominal aortic stent graft displacement. The methodology was successfully applied to clinical data of patients treated by endovascular aneurysm repair (EVAR) with different stent graft designs. This novel methodology enables provision of accurate data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Quantification of the cardiac-pulsatility-induced motion of the native vessel and RelayBranch was done by manual selection of points in the phase-averaged CT volume: the ventral and dorsal ascending aorta (1&2), the top of the aortic arch (3), the ventral and dorsal descending aorta (4&5), the end of the BCT (6&7), the BCT bifurcation (8), the LCCA (9&10), and the LCCA bifurcation (11) (Figure 2). The motion amplitudes, that is, pulsatility, of selected points in x —(lateral), y —(ventral-dorsal), and z —(caudal-cranial) directions were calculated by adding the deformation fields to the point coordinates as described and validated by Koenrades et al 5 with an error of ≤0.3 mm. The pathlength of each selected point was calculated as the sum of the distances between the point locations in subsequent phases.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of the cardiac-pulsatility-induced motion of the native vessel and RelayBranch was done by manual selection of points in the phase-averaged CT volume: the ventral and dorsal ascending aorta (1&2), the top of the aortic arch (3), the ventral and dorsal descending aorta (4&5), the end of the BCT (6&7), the BCT bifurcation (8), the LCCA (9&10), and the LCCA bifurcation (11) (Figure 2). The motion amplitudes, that is, pulsatility, of selected points in x —(lateral), y —(ventral-dorsal), and z —(caudal-cranial) directions were calculated by adding the deformation fields to the point coordinates as described and validated by Koenrades et al 5 with an error of ≤0.3 mm. The pathlength of each selected point was calculated as the sum of the distances between the point locations in subsequent phases.…”
Section: Methodsmentioning
confidence: 99%
“…Image analysis was performed using a previously established combination of an image registration and a segmentation algorithm 11 that was validated for motion estimation of endografts in ECG-gated CTA data. 9 The algorithm was customized to quantify motion and deformation of the Nellix stents, the chimney grafts and the stented branch vessels during the cardiac cycle. An overview of the applied methodology is shown in Fig 1 . First, the ECG-gated datasets with a slice thickness of 2.5 mm were interpolated in z-direction by spline interpolation to acquire submillimeter isotropic voxels.…”
Section: Methodsmentioning
confidence: 99%
“…8 The long-term stability of the endograft depends on its ability to withstand the repetitive stresses posed by the blood flow. Previous research has demonstrated that the degree of endograft motion may differ per fixation site and between devices, 9 which underlines the importance to understand the individual device dynamics to allow for adequate durability tests. To achieve long-term stability, it seems mandatory that the individual stents and chimney grafts move as a single unit.…”
mentioning
confidence: 99%
“…Validation on clinical data is widely used in the field of cardiovascular devices, especially in FEVAR, for example to predict fenestration rotation ( 47 ), iliac complications ( 49 ), or to validate numerical simulation of stent deployment ( 7 , 8 , 18 , 21 , 22 , 25 , 50 ). Other numerical methods have been validated by combining phantom and clinical data ( 11 , 12 , 29 , 51 ).…”
Section: Discussionmentioning
confidence: 99%